2021
DOI: 10.1177/08901171211060701
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Social Network Influences on Adult Physical Activity Using Social Network Analysis: A Systematic Review

Abstract: Objective Social network analysis (SNA) can measure social connectedness and assess impact of interpersonal connections on health behaviors, including physical activity (PA). This paper aims to systematically review adult PA studies using SNA to understand important social network concepts relative to PA. Data Source A search was performed using PsycINFO, MEDLINE, PubMed, and Web of Science. Study Inclusion and Exclusion Criteria To be included in the search, articles needed to 1) include a measure of PA, 2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
(78 reference statements)
2
14
0
2
Order By: Relevance
“…Some evidence exists on the role of friends in engagement in PA. According to systematic reviews, friends' PA levels have been seen to have a significant influence on an individual's PA level both for young people [50], and adults [51].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists on the role of friends in engagement in PA. According to systematic reviews, friends' PA levels have been seen to have a significant influence on an individual's PA level both for young people [50], and adults [51].…”
Section: Discussionmentioning
confidence: 99%
“…Our study examines the impact of OHC engagement on healthy lifestyle changes, thus contributing to the OHC. Moreover, through constructing a serially mediated model, our study helps explain how OHC engagement leads to positive lifestyle changes, echoing the call from Prochnow and Patterson ( 4 ).…”
Section: Discussionmentioning
confidence: 67%
“…Although it is not easy to make healthy lifestyle changes for many, researchers have found that socially supportive conditions help promote positive lifestyle behavior changes ( 3 , 4 ). Based on social network theory, studies have suggested that maintaining a good lifestyle (such as moderately intense physical activity, a balanced diet) often requires supervision and encouragement from strong ties, which generally refer to friends or family members ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…54 Copious social network research suggests PA behaviors "spread" through social ties, with individuals reporting similar PA behaviors as their network members over time. 23,55 Furthermore, residents mentioned the need for group or family activities/resources to promote PA within the community. Engaging the whole family in activities not only is essential for child PA but also encourages active participation from the adults and often older adults in the family.…”
Section: Discussionmentioning
confidence: 99%
“…Then the participant was asked several questions regarding each person they listed (also termed “alter”). This procedure is common to egocentric network analysis 23,46–48. Participants were asked how often they thought each person was physically active (response options: never, sometimes, often), how often they were physically active with the person (response options: never, sometimes, often), and whether this person was supportive of their health goals (response options: never, rarely, sometimes, usually, always).…”
Section: Methodsmentioning
confidence: 99%